Relation between intragastric bile acid concentration and mucosal abnormality in the stomach after vagotomy and gastroenterostomy for duodenal ulcer. Issue 5 (May 1984) - Watt, P C; Sloan, J M; Kennedy, T L
Abstract : A high incidence of possible premalignant conditions of the gastric mucosa has been reported in the postoperative stomach and it has been suggested that bile plays a role in their pathogenesis. Fifty eight patients who had had a vagotomy and gastrojejunostomy between 1957 and 1967 underwent endoscopy and biopsy. Subsequently, samples of fasting and postprandial gastric juice were taken from all patients for analysis of total bile acid. The patients were divided into three histological groups: group 1 (24 patients) had gastritis or mucosal atrophy but no more than mild dysplasia; group 2 (23 patients) had intestinal metaplasia in one or more biopsies; group 3 (11 patients) had moderate or severe dysplasia in one or more biopsies. Group 2 and group 3 patients had higher fasting intragastric bile acid concentrations than group 1 (p less than 0.01 in both cases). There was no difference between fasting bile acid concentrations in groups 2 and 3. In the postprandial phase groups 2 and 3 also had higher peak intragastric concentrations than group 1 (p less than 0.01 in both cases). Again, there was no significant difference between groups 2 and 3. It is concluded that there is a relation between mucosal abnormality in the postoperative stomach and intragastric bile acid concentration. The possible aetiological link between bile acid and these mucosal abnormalities is discussed.